Building government competitiveness in a post financial crisis: Comparing Malaysia and Indonesia from global competitiveness index perspective - Khalil, Samihah; Haryono, Endi (College of Law, Government and International Studies, Universiti Utara Malaysia., 2010)
The consequences of the 2007-2009 global financial crisis have been felt in virtually every economy. Most countries experiencing crisis would agree that it is government’s ultimate role to build competitiveness. This paper aims to compare country’s competitiveness between Malaysia and Indonesia, and governments’ effort in these countries to achieve that competitiveness. By competitiveness, we mean that government must do extremely well in managing and sustaining natural and human resources. Ranking 24th and 54th respectively in the Global Competitiveness Index 2009-2010, Malaysia and Indonesia require strategic reform and transformation, political and government programs to promote high levels of prosperity. Specifically, in this paper we will compare how Malaysia and Indonesia, under the leadership of Najib Tun Razak and Susilo Bambang Yudhoyono respectively, build their competitiveness through economic, political and administrative reforms. Malaysia and Indonesia, each have put forward new transformation plans in order to build competitiveness. This paper will analyze current achievements and review challenges to both countries’ recent transformation plans from the perspective of Global Competitiveness Report.